Seksualitas Perempuan dan Bahasa Perempuan Dalam Novel Larung Karya Ayu Utami Dan Banat Al-Riyadh Karya Rajaa Alsanea: Kajian Postfeminisme Luce Irigaray - Diah Fitriani; Zulfa Purnamawati (STIQ Amuntai, 2025)
The repression of female sexuality by the patriarchal system hinders women in recognising and expressing their sexuality fully. In response to this, Luce Irigaray emphasises the importance of creating a ‘female language’ that originates from the experiences of women's bodies and sexuality. This study analyses the construction of sexuality and female language in two novels, namely Larung by Ayu Utami (Indonesia) and Banat Al-Riyadh by Rajaa Alsanea (Saudi Arabia), which critically break the taboo of sexuality through the representation of female protagonists from different backgrounds. The research methods used were descriptive qualitative and comparative American approaches. The results show that Larung depicts sexuality as an autonomous right of women to enjoy and explore their sexuality freely and independently of patriarchal norms. The language of women in this novel uses metaphors that affirm women's subjectivity in sexual relationships. Meanwhile, sexuality in Banat Al-Riyadh is reduced to a mere form of service in marriage, and the language used by women displays subtle resistance and awareness stemming from wounds and trauma as victims in sexual relationships.